Facing the Challenges of Covid-19 in the Egyptian Banking Sector: The Role of Bricoleurs in Achieving Organizational Innovations via Learning through Improvisation - Abdo, Said; Edgar, David (Journal of Social Economics Research, 2021)
The COVID-19 pandemic posed many challenges for organizational survival across the world. Innovative capability became a key force in meeting such challenges and was most evident in Egypt’s banking sector. This paper explores, through semi-structured in-depth interviews with six general managers of multinational banks operating in Egypt, what innovation competences may enable organizational improvisers, or bricoleurs, to challenge, change, and achieve innovation during the COVID-19 pandemic. The results were analyzed through the lens of Senge’s five disciplines of learning organizations (Senge, 1990), with a particular consideration for the role of improvisation, and found that personal mastery is the dominant principle and is linked to achieving innovation in organizations. Within this element, the analysis also suggests that improvisation emerges from creativity, past experience, intuition, and distinct triggers, and that innovation competences appear as complementary elements of an organization’s behavior, encapsulated as a form of bricolage when challenges arise and resource constraints prevail. The results suggest that a set of practices and strategies could be applied by general managers to meet the challenges they face involving constraints, such as a shortage of human resource, and that improvisation can form one of their key innovation competences.